Juridical analysis of religious blasphemy crimes through smartphone applications based on the information and electronic transactions (ite) - SIREGAR, GOMGOM T.P; LUBIS, MUHAMMAD RIDWAN (The journal of contemporary issues in business and government, 2021)
The presence of Law No. 11 of 2008 on Information and Electronic Transactions as revised by Law No. 19 of 2016 on Amendments to Law No. 11 of 2008 on Information and Electronic Transactions, should be expected to be able to direct Indonesians to be more intelligent in building communication and behaving on social media which is now a new social reality in human civilization in the modernization era. This study aims to find out and analyze about the crime of blasphemy through social media and the application of the law and the impact of the application of the ITE Law law on public legal awareness. This research is normative legal research using case approach, legal approach and conceptual approach. This research is descriptive analytically using qualitative analysis.